Low serum levels of vitamin B12 in older adults with normal nutritional status by mini nutritional assessment - Araújo, DA (2016)
Undernutrition as well as low levels of vitamin B12 and folic acid are common problems among older adults. However, recommended routine nutritional status assessment tools may result in inadequate vitamin serum levels to go unnoticed. Therefore, the aim of this study is to evaluate the inadequacy of serum levels of vitamin B12 and folic acid within Mini Nutritional Assessment (MNA) classification categories among older adults. A cross-sectional study was conducted with 97 older adults residing in care homes in Portugal. Undernutrition was identified through the MNA, and serum levels of vitamin B12 and folic acid were measured using chemiluminescence. Cognitive function, depressive symptoms and functional characteristics were also assessed using the Abbreviated Mental Test Score, the Epidemiologic Studies Depression Scale and the Barthel Index, respectively. The mean age of older adults was 82.2 (6.3) years; 3.1% were undernourished and 26.8% were at undernutrition risk. In the MNA normal nutritional status group, 11.8% presented vitamin B12 deficiency (<200â pg/ml), 32.4% had low serum levels (200â 400â pg/ml) and 4.4% had folic acid deficiency (<3â ng/ml). A high proportion of older adults with low serum levels of vitamin B12 presenting normal nutritional status by MNA was identified. This finding emphasizes the need to evaluate serum vitamin B12 levels, independently of the MNA results.European Journal of Clinical Nutrition advance online publication, 23 March 2016; doi:10.1038/ejcn.2016.33. Â© 2016 Macmillan Publishers Limited